Epigenetic Marks at the Ribosomal DNA Promoter in Skeletal Muscle Are Negatively Associated With Degree of Impairment in Cerebral Palsy - von Walden, Ferdinand; Fernandez-Gonzalo, Rodrigo; Pingel, Jessica; McCarthy, John; Stål, Per; Pontén, Eva (Frontiers in Pediatrics, 2020)
Introduction Cerebral palsy (CP) is the most common motor impairment in children. Skeletal muscles in individuals with CP are typically weak, thin and stiff. If epigenetic changes at the ribosomal DNA (rDNA) promoter are involved in this dysregulation remains unknown. Methods Skeletal muscle samples were collected from nineteen children with CP and 10 typically developed (TD) control children. Methylation of the rDNA promoter was analyzed using the Agena Epityper Mass array and gene expression by qRT-PCR. Results Biceps muscle ribosome biogenesis was suppressed in CP as compared to TD. Average methylation of the rDNA promoter was not different between CP and TD but negatively correlated to elbow flexor contracture in the CP group. Discussions We observed a negative correlation between rDNA promoter methylation and degree of muscle contracture in the CP group. Children with CP with more severe motor impairment had less methylation of the rDNA promoter compared to less affected children. This finding suggests the importance of neural input and voluntary muscle movements for promoter methylation to occur in the biceps muscle.